FACTORS ASSOCIATED WITH UNDERNUTRITION AMONG CHILDREN WITH SICKLE CELL DISEASE ATTENDING THE SICKLE CELL CLINIC IN MULAGO NATIONAL REFERRAL HOSPITAL, UGANDA. A CROSS SECTIONAL STUDY. - Rosta Asiimwe; Rornald Muhumuza; Richard Kajura; Adoke Yeka (Student's Journal of Health Research, 2023)
Background:  Sickle cell disease (SCD) is among the neglected non-communicable diseases, which significantly contributes to early childhood mortality. In Uganda, over 20,000 children are estimated to be sicklers. Undernutrition is common among children with SCD and contributes to increased morbidity and mortality. There is a paucity of data on the prevalence of undernutrition and associated factors in Uganda. Objective:  To assess the extent of undernutrition and related factors among children aged 5-12 years with SCD attending the sickle cell clinic at Mulago National Referral Hospital (MNRH), Uganda.   Methods:  A hospital-based cross-sectional study was conducted. A total of 270 children with SCD attending the sickle cell clinic at MNRH were recruited consecutively between May and June 2017. The nutritional status of the children was assessed by BMI-for-age (wasting) and height-for-age (stunting) z-scores calculated using STATA in accordance with WHO reference. Binary logistic regression was conducted using odds ratios with 95% CI to measure the strength of association among the predictors. Results:  About 11.4% were wasted and 13.7% were stunted. Wasting was significantly associated with older age (10-12 years) (AOR=4.27, CI=2.20-8.29) and living in a female-headed household (AOR=0.39, CI=0.16-0.92). Stunting was significantly associated with older age (10-12 years) (AOR=2.90, CI=1.39-6.06).  Conclusion:  Wasting and stunting were prevalent among children with SCD attending MNRH. The factors associated with undernutrition were older age and living in a female-headed household.  Recommendations:  Interventions like skills-based nutrition education integrating older children and enhancement of women's control of household resources by improving the social economic status of caretakers through business training and providing vocational skills can improve undernutrition in children with SCD.